The role of target 3D-reconstructions when analysyng qualitative characteristics of the surface of circular-shaped growth in the lungs - V. G. Kolmogorov; V. K. Konovalov; S. L. Leonov; M. N. Lobanov (Бюллетень сибирской медицины, 2017)
The purpose of this paper is to improve the accuracy of X-ray diagnostics of circular-shaped growth (CSG) by developing computed tomographic semiotics of qualitative characteristics of its surface and the state of the surrounding bronchi using target 3D-reconstruction.Material and methods. 560 patients at the age of 3–89 years were examined. Target 3D reconstruction was carried out with the use of 3D Fly Through program (Toshiba Medical Systems, Japan) which removed the tissue surrounding CSG at a distance of 5–10 mm from the outer boundaries.CSG was inscribed into a cube. In case of the primary central and peripheral lung cancer a number of patients with severe rough surface of CSG prevailed over a number of patients with slightly rough surface was detected. In case of infiltrative tuberculosis, pneumonia, echinococcus, retention cysts the prevalence of a number of patients with slightly rough surface of CSG over a number of patients with rough surface was identified. In case of single cancer metastases, single and multiple tuberculomas the prevalence of a number of patients with non-uniform smooth surface of CSG over a number of patients with uniform smooth surface was identified. In case of multiple cancer metastasis, focal tuberculosis, cysticercosis the prevalence of a number of patients with a uniform smooth surface of CSG over a number of patients with uneven smooth surface was identified. In case of benign tumors, eosinophilic infiltrate, gamartohondroma, aspergilloma, chronic abscess, intrapulmonary hematoma there was not difference between the number of patients with a uniform smooth surface of CSG and a number of patients with uneven smooth surface. In case of primary lung cancer metastasis, single and multiple tuberkulomas, echinococcus, cysticercosis there was a prevalence of the number of patients with expressed deformed bronchi surrounding CSL over a number of patients with moderately deformed bronchi. In case of infiltrative and focal tuberculosis there was prevalence of a number of patients with moderately deformed bronchi surrounding CSL over a number of patients with expressed deformed bronchi.Results. In case of pneumonia, benign tumors, retention cysts, gamartohondroma, aspergilloma, chronic abscesses, and intrapulmonary hematomas there was no difference between the number of patients with expressed deformed bronchi surrounding CSL, and a number of patients with moderately deformed bronchi. Patients with single and multiple metastases, eosinophilic infiltration, bronchi surrounding CSL were not changed. It is necessary to develop a software that allows quantitatively characterize the surface of CSL and the degree of deformation of the surrounding bronchi.